Sodium Tanshinone II Sulfonate A Ameliorates Hypoxia-Induced Pulmonary Hypertension - Bao, Ya-Ru; Chen, Jing-Wei; Jiang, Yan; Wang, Lin-Hui; Xue, Rong; Qian, Jin-Xian; Zhang, Guo-Xing (Frontiers in Pharmacology, 2020)
Background Pulmonary hypertension (PH) remains a prevalent disease globally. Sodium tanshinone II sulfonate A (STS) has been used in clinical treatment of PH. Aims The aim of the present study was to investigate the effect of sodium STS treatment on hypoxia-induced PH and related mechanisms. Methods Male Sprague-Dawley rats were housed in a hypoxic chamber with an oxygen concentration of 10 ± 1% for 8 h a day over 21 days. Rats were treated with either STS (low-dose: 10 mg/kg or high-dose: 30 mg/kg) or LY294002 (which is an inhibitor of PI3K). Pulmonary arterial pressure (PAP) was measured, right ventricular hypertrophy parameters were monitored, lung edema parameters were measured, and pathological changes were observed by hematoxylin-eosin (HE) staining. Protein expressions of apoptosis, and PI3K/AKT/mTOR/autophagy pathways in rat lung tissue were examined by western blot. Levels of the pro-inflammatory factors IL-6, IL-8, TNF-α in lung tissues of rats were measured using an enzyme linked immunosorbent assay (ELISA). Results Results of our study demonstrate that persistent exposure to hypoxic conditions increased PAP, right ventricular hypertrophy, lung edema, parameters of lung vascular proliferation and decreased the ratio of Bax/Bcl-2. Furthermore, hypoxic conditions activated the PI3K/Akt/mTOR pathway, inhibited autophagy, and elevated abundance of inflammatory factors in rat lung tissue. Treatment with STS resulted in a dose-dependent decrease in PAP, right ventricular hypertrophy, lung edema, lung vascular proliferation and reversed hypoxia induced lung tissue protein expression and pro-inflammatory factors in rat lung tissue. In addition, hypoxia-induced increases in PAP, cardiac hypertrophy, and lung expression of the proteins PI3K/Akt/mTOR/autophagy pathway were partially reversed by treatment with LY294002. Conclusions STS alleviates hypoxia-induced PH by promoting apoptosis, inhibiting PI3K/AKT/mTOR pathway, up-regulating autophagy, and inhibiting inflammatory responses.